Lack of Clinically Relevant Effect of Bictegravir (BIC, B) on Metformin (MET) Pharmacokinetics (PK) and Pharmacodynamics (PD). (4th October 2017) - Custodio, Joseph; West, Steve; Yu, Amanda; Martin, Hal; Graham, Hiba; Quirk, Erin; Kearney, Brian
Abstract: Background: BIC is a novel integrase inhibitor coformulated with emtricitabine (F) and tenofovir alafenamide (TAF) for treatment of HIV. MET is first-line therapy in diabetic HIV patients. In vitro, BIC inhibits renal transporters OCT2 and MATE1, which affect MET disposition. This study evaluated the effect of BIC on the PK and PD of MET following coadministration with the B/F/TAF. Methods: This was a Phase 1, blinded, placebo-controlled, crossover study in 32 healthy subjects randomized 1:1 to either B/F/TAF or placebo QD for 9 days followed by a 3-day washout. Following 4 days of B/F/TAF or placebo, subjects received 850 mg MET at 12 hours postdose of B/F/TAF or placebo, and 500 mg BID for 4 additional days. Plasma and urine PK of MET were assessed on the last treatment day (Days 9 and 21 for B/F/TAF or placebo). Oral glucose tolerance test was performed before (Days 5 and 17) and after MET (Days 9 and 21). MET PD endpoints including plasma glucose, active Glucagon-Like Peptide 1 (GLP-1) and lactate were assessed after glucose intake. Geometric mean ratios (GMR) and 90% confidence intervals (CIs) for MET PK were calculated for B/F/TAF vs. placebo. Comparisons of PD responses within treatments (before vs. after MET) and comparisons between treatments (B/F/TAF vs. placebo) were done via nonparametric Wilcoxon signed-rank test ( P > 0.05 denotes non-significance). Results: MET plasma AUCtau was increased 39% (%GMR [90% CI]: 139 [131, 148]) with B/F/TAF vs. placebo, with no change in median plasma t1/2 (B/F/TAF: 6.4 hours; placebo: 7.1 hours). MET renal clearance decreased 31% with B/F/TAF vs. placebo. Following MET administration, statistically significant reduction of plasma glucose, and increase of plasma active GLP-1 and lactate levels relative to baseline were observed (P < 0.001) confirming their utility as PD endpoints. Importantly, PD responses were not statistically different when MET was administered with B/F/TAF vs. placebo (p >0.05). Conclusion: Inhibition of renal transporters OCT2/MATE1 by BIC led to a modest increase of MET plasma exposure upon coadministration with B/F/TAF; however, the PD characteristics of MET were not significantly affected by B/F/TAF relative to placebo. Based on these findings, prospective dose adjustment/restriction of MET is not required upon coadministration with B/F/TAF. Disclosures: J. Custodio, Gilead Sciences: Employee and Shareholder, Salary; S. West, Gilead Sciences: Employee and Shareholder, Salary; A. Yu, Gilead Science: Employee, Salary; H. Martin, Gilead Sciences: Employee, Salary; H. Graham, Gilead Sciences: Employee and Shareholder, Salary; E. Quirk, Gilead: Employee and Shareholder, Salary; B. Kearney, Gilead: Employee and Shareholder, Salary